What is planted in the restoration of the Atlantic Forest: floristic and functional analysis - Almeida, Crislaine de (2022)
Forest deforestation causes loss of taxonomic diversity and alteration in ecological processes. Forest restoration plantings aims to conserving landscape species, but if the planted species do not represent the local flora, native species can be lost, leading to biotic homogenization. Species planted for forest restoration are those available in nurseries and prioritized for the ease of obtaining and production, creating a filter called of restoration species pool. The Brazilian Atlantic Forest is one of the worlds hotspots for biodiversity conservation and where many forest restoration initiatives are developed. Our objective in this work was to compare the floristic and functional diversity between lists of forest restoration plantings and forest remnants of the Atlantic Forest. We used a database with 1073 lists of restoration plant carried out in the Atlantic Forest from 2002 to 2018 by the Click Tree program and 268 remnants of the Treeco secondary database that has floristic and phytosociological surveys carried out in forest remnants of the Atlantic Forest. Analyzes were carried out for the entire Atlantic Forest and for three forest types separately: Mixed Ombrophilous Forest, Ombrophilous Dense Forest, and Semideciduous Seasonal Forest. In the first chapter we evaluated if restoration plantings represent dispersal syndromes, ecological groups and the proportion of nitrogen-fixing and threatened species compared to forest remnants. We found that 423 tree species are planted in restoration plantings, which represents less than 8% of the Atlantic Forest flora. Restoration plantings had a higher proportion of nitrogen fixing species (15% in plantings vs. 8% in remnants) and individuals than forest remnants, but underrepresentation of secundary species (85% vs. 67%) animal-dispersed species (50% vs. 71%) and threatened species (18 in plantings vs. 83 in remnants). In the second chapter we tested whether the planted species are representing the diversity of forest remnants. We calculated the Simpson dominance index and the dissimilarity index for plantings and remnants and between plantings and remnants for each forest type and for forest types comparing plantings and remnants. To assess the ordering of plantings and remnants according to their floristic composition, we calculated a non-metric multidimensional scale analysis (NMDS) and the PERMANOVA post-hoc test, and to infer whether floristic dissimilarity increases with distance and similarly for forest remnants and forest plantings, we calculated generalized linear models (GLMs) using the Bray Curtis index. Our results showed that forest plantings are more similar to each other than to the remnants, that is, we face a process of biotic homogenization, since the planted species did not represent remnant species. We recommend including more endangered, endemic and underrepresented species in forest restoration.